Role of magnetic field evolution on filamentary structure formation in intense laser–foil interactions. (13th March 2019) - King, M.; Butler, N. M. H.; Wilson, R.; Capdessus, R.; Gray, R. J.; Powell, H. W.; Dance, R. J.; Padda, H.; Gonzalez-Izquierdo, B.; Rusby, D. R.; Dover, N. P.; Hicks, G. S.; et al.
Abstract : Filamentary structures can form within the beam of protons accelerated during the interaction of an intense laser pulse with an ultrathin foil target. Such behaviour is shown to be dependent upon the formation time of quasi-static magnetic field structures throughout the target volume and the extent of the rear surface proton expansion over the same period. This is observed via both numerical and experimental investigations. By controlling the intensity profile of the laser drive, via the use of two temporally separated pulses, both the initial rear surface proton expansion and magnetic field formation time can be varied, resulting in modification to the degree of filamentary structure present within the laser-driven proton beam.